The effects of childhood trauma on adolescent hippocampal subfields. (May 2019) - Malhi, Gin S; Das, Pritha; Outhred, Tim; Irwin, Lauren; Gessler, Danielle; Bwabi, Zina; Bryant, Richard; Mannie, Zola
Objective: Mood disorders are more common among girls and typically emerge during adolescence. The precise reasons for this are unknown, but among the many mechanisms implicated are stress-induced hippocampal structural changes during this developmental stage. The hippocampus is a complex structure comprised of subfields that develop differentially and respond variably to stress and childhood adversity, both of which are risk factors for mood disorders. To better understand vulnerability to mood disorders, we investigated a cohort of adolescent girls and determined volumetric changes in their hippocampal subfields to elucidate the potential effects of childhood trauma. Methods: Of the 229 participants, 201 girls (aged 12–17 years) fulfilled our analysis inclusion criteria. Of these, 76 had been exposed to higher emotional trauma (emotional abuse or neglect). The girls underwent high-resolution structural magnetic resonance imaging scans, and hippocampal subfield volumes were measured using FreeSurfer. We compared hippocampal subfield volumes in those exposed to higher emotional trauma and those exposed to minimal emotional trauma, at three time-points of adolescent development: early (12–13 years), mid (14–15 years) and late (16–17 years). Results: Mid-adolescent girls exposed to higher emotional trauma had significantly smaller left CA3 volumes than minimal emotional trauma girls ( p = 0.028). Within the minimal emotional trauma group, mid-adolescents had significantly larger left CA3 volumes than early ( p = 0.034) and late ( p = 0.036) adolescents. Within the higher emotional trauma group, early adolescents had significantly larger left CA3 volumes than late adolescents ( p = 0.036). Conclusion: In our exploratory study, we observed higher emotional trauma–induced volume changes in the left CA3 hippocampal subfield, which varied depending on age, and may ultimately produce deficits in behavioural, cognitive and emotional processes. We propose that these changes (1) may provide a mechanism through which vulnerability to mood disorders may be increased in adolescent girls, and (2) may signal the best times to implement targeted prevention interventions.